Strategic choice of entry mode into China: the case of video games firms - Ukrit, Nuchana (2008)
Entry mode decision is a vital strategy for multinational firms doing business in foreign country, especially in a transitional economy. This study examines the determinants of strategic choice of entry mode from resource-based view perspectives, and firm- and country- specific factors. The research posits that R&D intensive firm's strategic mode of entry into China is influenced by both resource-based view of the firms and the determinants of entry mode. Based on video games console firm's strategic choice of entry mode in China, the study finds that there is a supporting link between resource-based view perspectives, and determinants of firm- and country- specific factors. This dissertation confirms that strategic entry mode choice into China for R&D firms in video games console business should be considered by multiple theoretical perspectives.